Risk of Occult Uterine Sarcoma in Women Undergoing Hysterectomy for Benign Indications. Issue 3 (March 2016) - Kho, Kimberly A.; Lin, Ken; Hechanova, Martin; Richardson, Debra L.
Abstract : OBJECTIVE: To estimate the frequency of unsuspected sarcoma identified postoperatively in women undergoing surgery for benign gynecologic indications at our institution. METHODS: Patients undergoing hysterectomy for benign gynecologic indications from 2000 to 2014 at our institution were identified. Patients who did not have a preoperative suspicion for malignancy and were found to have uterine sarcoma on pathology postoperatively were considered to have an occult uterine sarcoma. Relevant clinical and pathologic data were collected for this retrospective cohort study. RESULTS: A total of 10, 119 hysterectomies for benign gynecologic indications were performed between 2000 and 2014. Among these, nine patients were found to have uterine sarcoma, with an overall rate 1 in 1, 124 (95% confidence interval 1/592–1/2, 457). These malignancies included five leiomyosarcomas, two endometrial stromal sarcomas, and two uterine adenosarcomas. Median age was 39 years (range 25–53 years). Among women found to have occult sarcoma, hysterectomy was performed as a primary indication for abnormal bleeding (77.8%) and leiomyomas (22.2%). Cases included six total abdominal hysterectomies, two total vaginal hysterectomies, and one supracervical hysterectomy. One case required manual morcellation during abdominal hysterectomy. Power morcellation was not used in any of the cases. CONCLUSION: In summary, occult uterine sarcoma occurs in 0.089% or 1 in 1, 124 hysterectomies for benign indications in our population. The frequency is lower than the rate derived in earlier reports and by the U.S. Food and Drug Administration in their pooled analysis. Abstract : The frequency of occult uterine sarcoma in women undergoing hysterectomy for benign indications at our institution is 0.89% or 1 in 1, 124, lower than previously reported.